2011
DOI: 10.1111/j.1600-0625.2010.01217.x
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage oligomeric matrix protein (COMP) forms part of the connective tissue of normal human hair follicles

Abstract: Hair follicle cycling is driven by epithelial-mesenchymal interactions (EMI), which require extracellular matrix (ECM) modifications to control the crosstalk between key epithelial-and mesenchymal-derived growth factors and cytokines. The exact roles of these ECM modifications in hair cycle-associated EMI are still unknown. Here, we used differential microarray analysis of laser capture-microdissected human scalp hair follicles (HF) to identify new ECM components that distinguish fibroblasts from the connectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 57 publications
(88 reference statements)
0
7
0
Order By: Relevance
“…COMP was found to be dependent on the hair cycle, expressed during telogen and early anagen and degraded during catagen [ 38 ]. From our results, COMP was upregulated during spaceflight in three astronauts.…”
Section: Discussionmentioning
confidence: 99%
“…COMP was found to be dependent on the hair cycle, expressed during telogen and early anagen and degraded during catagen [ 38 ]. From our results, COMP was upregulated during spaceflight in three astronauts.…”
Section: Discussionmentioning
confidence: 99%
“…There were 13 differentially expressed genes were enriched in MAPK signaling pathway. It has been reported that the MAPK signaling pathway may be related to hair color formation (Schellenberger et al, 2011). MAPK signaling pathway plays an important role in regulating hair cycle and self-renewal of hair follicle stem cells (Akilli ÖztĂŒrk et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…To date, transcriptional profiling of HF cells has been conducted in mice and rats, effectively revealing known and new receptors and the signaling pathways involved in the maintenance of murine HF stem cells (Morris et al, 2004;Tumbar et al, 2004;Ishimatsu-Tsuji et al, 2005;Trempus et al, 2007;Umeda-Ikawa et al, 2009). Microarray studies that use human HFs have so far focused on fossile mRNA (Tochio et al, 2011), compared HF fibroblast populations (Goodarzi et al, 2010;Ariza de Schellenberger et al, 2011), and plugged incomplete HFs (Kim et al, 2006) or HFs exposed to ex vivo pharmacological experiments (Gaspar et al, 2010). Here we provide an intra-individual comparison using native microdissected HFs with melanocytes as indicators of biological age.…”
Section: Discussionmentioning
confidence: 99%